1978
DOI: 10.1902/jop.1978.49.7.357
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Localized Gingival Recessions: Part II. Coronally Repositioned Flap with a Free Gingival Graft

Abstract: Fourteen teeth with localized gingival recessions were treated using a coronally repositioned flap with a free gingival graft (Bernimoulin, 1973). The second step of the procedure was performed 1 month after the free gingival graft was done. Clinical measurements of the recession, sulcus depth and keratinized gingiva were taken preoperatively and at 30, 90 and 180 days after surgery. A mean reduction in the recession of 2.73 mm was obtained after 6 months, which was equivalent to a 64% decrease of the original… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
3

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 6 publications
1
23
0
3
Order By: Relevance
“…When more than one study reported follow-up data on the same patients, 45,46,65,69,70 we reported the data extracted from the most recent study; in one study, 65 we chose the shorter follow-up because it covered a larger number of patients.…”
Section: Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…When more than one study reported follow-up data on the same patients, 45,46,65,69,70 we reported the data extracted from the most recent study; in one study, 65 we chose the shorter follow-up because it covered a larger number of patients.…”
Section: Data Collectionmentioning
confidence: 99%
“…Trombelli et al 57 (CAF+TRC+FG/CAF+TRC) Pini-Prato et al 59 (CAF+Pol/CAF+RP) Pini-Prato et al 61 (CAF+FTens/CAF no FTens) CTG Bouchard et al 25 (CTG+TRC/CTG+CARC) Borghetti and Louise 24 (CTG+DPF/no treatment) Bouchard et al 32 (CTG+TRC/CTG+CARC) Harris 31 (FGG knife method/FGG parallel incision methods) Harris 43 (CTG/acellular dermal matrix) GTR Trombelli et al 77 (ePTFE/ePTFE+TRC+FG) Roccuzzo et al 78 Guinard and Caffesse 45 Caffesse and Guinard 65 Caffesse and Guinard 46 Kunjamma et al 8 Laney et al 14 Ricci et al 28 Harris 29 Zucchelli et al 33 Jepsen et al 34 Trombelli et al 37 Harris 38 Borghetti et al 40 Tatakis and Trombelli 41 Rosetti et al 42 Trombelli et al 58 Amarante et al 62 Sbordone et al 10 Daniel and Cheru 12 Jahnke et al 15 Paolantonio et al 17 1. If the reporting of probing depth (PD) before and after treatment is included, only 59 out of 90 articles (65.6%) would have been accepted.…”
Section: Cafmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology used and the results obtained with the individual techniques have been reported separately. 3,6 All data obtained were analyzed statistically to deter mine the significance of the results after the use of the lateral sliding flap and the coronally repositioned flap. The results with both techniques were compared to test the following hypotheses:…”
mentioning
confidence: 99%